Lessons in Mind Control: Trends in Research on the Molecular Mechanisms behind Parasite-Host Behavioral Manipulation - Herbison, Ryan E. H. (Frontiers in Ecology and Evolution, 2017)
Scientific and public interest in host manipulation by parasites has surged over the past few decades, resulting in an exponential growth of cases where potential behavioural manipulation has been identified. However, these studies dwarf the number of genuine attempts to elucidate the mechanistic processes behind this behavioural manipulation. Ultimately, this imbalance has slowed progress in the study of the mechanisms underlying host manipulation. As it stands, research suggests that the mechanisms of host manipulation fall into three categories: immunological, genomic/proteomic and neuropharmacological, and forth potential category: symbioant-mediated manipulation. After exploration of the literature pertaining to these four pathways, four major trends become evident. First and foremost, there is a severe disconnect between the observed molecular and behavioural shifts in a parasitized host. Indeed, very rarely a study demonstrates that molecular changes observed in a host are the result of active manipulation by the resident parasite, or that these molecular changes directly result in behavioural manipulation that increases the parasite’s fitness. Secondly, parasites may often employ multiple pathways in unison to achieve control over their hosts. Despite this, current scientific approaches usually focus on each manipulation pathway in isolation rather than integrating them. Thirdly, the relative amount of host-parasite systems yet to be investigated in terms of molecular manipulation is staggering. Finally, as a result of the aforementioned trends, guiding mechanisms or principles for the multiple types of behavioural manipulation are yet to be found. Researchers should look to identify the manipulative factors required to generate the molecular changes seen in hosts, while also considering the ‘multi-pronged’ approach parasites are taking to manipulate behaviour. Assessing gene expression and its products during transitional periods in parasites may be a key methodological approach for tackling these recent trends in the host manipulation literature.